2021
DOI: 10.1021/acssuschemeng.1c03823
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Rich MoO3 Nanobelt Cathode for a High-Performance Hybrid Alkali/Acid Zn-MoO3 Rechargeable Battery

Abstract: Protons (H+) and hydroxide ions (OH–) are regarded as ideal charge carriers for rechargeable batteries thanks to their small size, high ion mobility, low cost, and wide flexibility compared to the metal ions. However, the implementation of storage of both H+ and OH– in one electrochemical energy device faces grand challenges due to incompatibility between H+ and OH–. Herein, we report an alkali-acid Zn-MoO3 hybrid battery that employs H+ and OH– as charge carriers of the cathode and anode, respectively, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…cathode in acid (Figure 5g). [22] Both electrodes show redox activity at their individual potential windows from the CV curves (Figure 5h), indicating the availability and feasibility of fabricating an alkaline-acidic dual-ion ZnÀ MoO 3 battery. Zn would be oxidized to Zn(OH) 4 2À with consumption of OH À on the anode and MoO 3 would be reduced H x MoO 3 with consumption of H + on the cathode during the discharging process, while H + and OH À would be generated on the cathode and anode, respectively during the charging process.…”
Section: Insertion Mechanismmentioning
confidence: 92%
“…cathode in acid (Figure 5g). [22] Both electrodes show redox activity at their individual potential windows from the CV curves (Figure 5h), indicating the availability and feasibility of fabricating an alkaline-acidic dual-ion ZnÀ MoO 3 battery. Zn would be oxidized to Zn(OH) 4 2À with consumption of OH À on the anode and MoO 3 would be reduced H x MoO 3 with consumption of H + on the cathode during the discharging process, while H + and OH À would be generated on the cathode and anode, respectively during the charging process.…”
Section: Insertion Mechanismmentioning
confidence: 92%
“…Controllably constructing defects in electrodes can fundamentally increase their electrical conductivity, accelerate ions diffusion and charges transfer, decrease the stress and electrostatic repelling forces between adjacent layers, and directly overcome migration and diffusion obstacles. [141][142][143] On the other hand, introducing defects can provide sufficient active sites for ions or intermediates adsorption and reaction, which is beneficial for maintaining their structural stability and flexibility. Galvanostatic intermittent titration results revealed that the ammonium vanadate cathode with oxygen-defect had a satisfied Zn 2+ diffusion coefficient of ≈10 −9 cm 2 s −1 under −30 °C (Figure 12f,g), because the deficient oxygen atoms in bilayered structure distinctly decreased the zinc diffusion energy barrier and improved its structural stability, delivering a cyclic stability of 2600 cycles life at 2 A g −1 under −30 °C.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[52] An H + DIB with OH À as the anion carrier has been assembled using a device containing cathode and anode chambers separated by Nafion membrane that allows only proton to pass through. [54] Defect-rich MoO 3 porous nanobelt is applied as cathode in electrolyte of 2 m H 2 SO 4 solution, and zinc is applied as anode in alkali electrolytes containing 4 m NaOH and 0.1 m Zn(CH 3 COO) 2 solution. The intercalation/de-intercalation of H + takes place in the cathode side by Equation (2):…”
Section: Non-metal Ionsmentioning
confidence: 99%